2023
DOI: 10.1111/ctr.14889
|View full text |Cite
|
Sign up to set email alerts
|

Trends in organ donation and transplantation over the past eighteen years in Iran

Abstract: Background This article will review the trends in organ donation over the past 18 years in Iran. Material and methods All donation and transplantation statistics were extracted by reviewing the Organ Procurement and Transplantation database of the Ministry of Health of Iran from 2002 to 2019. Results Iran's national deceased donation rate from 2002 to 2019 increased 19.06‐fold from .75 to 14.3 per million population (PMP). After the beginning of the COVID‐19 pandemic, the rate of organ donation in Iran decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…We read with great interest the article by Dehghani and colleagues 1 on trends in organ donation and transplantation over past 18 years in Iran. Iran has made significant progress in the last 20 years to build an infrastructure to promote deceased donation from brain death donors.…”
Section: E T T E R T O T H E E D I T O R Transplantation In Iranmentioning
confidence: 99%
“…We read with great interest the article by Dehghani and colleagues 1 on trends in organ donation and transplantation over past 18 years in Iran. Iran has made significant progress in the last 20 years to build an infrastructure to promote deceased donation from brain death donors.…”
Section: E T T E R T O T H E E D I T O R Transplantation In Iranmentioning
confidence: 99%
“…Conversely, negative family attitudes toward organ donation significantly hinder the consent process [ 9 ]. Research in Iran has shown that family members often have the final decision-making power regarding the donation of their children’s organs, with the healthcare system playing an essential role in encouraging individuals to register for and carry donor cards [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also mention in our paper, Iran has an Opt-in consent legislation system. 1 The final decision for organ donation is given by families.…”
mentioning
confidence: 99%